Dinâmica nutricional em um povoamento de Pinus taeda L., Rio Grande do Sul, Brasil - Lopes, Vicente Guilherme (2013)
The knowledge of nutrition dynamics in forest stands provides basis for forest implementation, using the principles of sustainable forests. This study investigated the nutrition dynamics in a pine stand, deployed in 1993, without fertilization, from seedlings at 3 m x 2 m spacing. At 18 years of age, 701 trees remained planted per hectare with mean diameter 29.4 cm, mean height 19.3 m, dominant height 19.9 m, basal area 48.5 m² ha-1 and volume with bark 460.8 m³. To study rainfall distribution, nutrient flows and variation, and nutrient content in the soil solution, we used rainwater collectors and lysimeters installed in the pine stand and in an adjacent area of natural grassland characterized by high diversity of native plant species. Were also used collectors to obtain plant litter. In 2011, we inventoried the tree biomass and litter layer in the pine stand. The average precipitation volume (P) in the study area was 2081.5 mm yr-1. In the pine stand, throughfall (T) was 1280.1 mm yr-1, stemflow (S) 89.0 mm yr-1, totaling 1369.1 mm year-1 (T + S), evidencing a canopy interception of 34.5%. The annual total contribution of each nutrient followed the decreasing order: Cl > Na > K > S > Ca > N > Mg > P. The annual contribution (kg ha-1 yr-1) from T + S was 29.39 (Cl), 21.73 (Na), 18.04 (K), 17.02 (S), 9.82 (Ca) 5.64 (C) 3.44 (Mg) and 0.84 (P). In the pine stand, the decreasing content of elements in the soil solution at 30 cm was: Cl > Na > Ca > S > Mg > K > NO3- > NO2- > P, and at 60 cm: Ca > Cl > Na > S > K > Mg > P > NO3- > NO2-. In the pasture area, all analyzed ions in the soil solution showed lower contents than those found in the pine stand. The sequence of decreasing biomass accumulation was: stem wood > stem bark > living branch > dead branch > needles > pointer wood > pointer bark. The biomass of litter was 21.33 Mg ha-1. Considering the tree biomass above ground, the nutrient content in kg ha-1 was: 421.65 N, 39.37 P, 173.46 K, 176.59 Ca, 55.47 Mg, 43.27 S, 91.91 Na, 0.79 Cu, 8.83 Fe, 27.51 Mn and 1.06 Zn. The annual mean of litterfall was 5.85 Mg ha-1. Exports of all nutrients rose as the intensity of biomass use increased. The sequence of nutrients, regarding the risk of limiting productivity, due to intense levels of biomass use was: N > P > K > Mg > Ca.